Kinerja Kelompok Tani dalam Program Lembaga Distribusi Pangan Masyarakat (LDPM) dan Hubungannya dengan Produksi dan Pendapatan Petani Padi di Kecamatan Makarti Jaya Kabupaten Banyuasin - Sriati Sriati; Nukmal Hakim; M. Arby (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Sriati, et al. Farmer Groups Performance on Program of Institution of Community Food Distribution (LDPM) and the Correlation with Paddy Farmers Production and Income in Makarti Jaya District, Banyuasin Regency. JLSO 5(2):208-218. The research was aimed to: (1) measure the Farmer Groups Performance on Institution Community Food Distribution (LDPM) Program, (2) measure the production and income paddy farmers, and (3) to analyze the corelation between Farmer Groups Performance level with paddy farmers income. Research was conducted by survey method and continued by descriptve and corelation analysis. Responden were consisted of 45 farmers, from 9 cluster of Sri Rejeki’s farmergroup (respectevely 5 farmers). The result showed that: (1) levProduksi Petani padi peserta LDPM rata-rata 5834 kg/lg/th (produkstivitas 2946 kg/ha) dan pendapatan rata-rata Rp 6.304.884,00 /ha/th; dan (3) tel of performane group farmers was on high category with score 35,91 (79,8%); (2) Production of paddy farmers LDPM participants average 5834 kg/lg/year (productivity 2946 kg/ha) and average income Rp 6.304.884,00/ha/year; and (3) there was a Rank Spearman correlation coeficient (Rs) = 0,81 between the level of performance farmers group with level of income paddy farmers with significant level a 0,05.